Beta-glucans supplementation for sows during gestation and lactation - Julia Delpupo Coelho; Pedro Henrique Watanabe; Tiago Silva Andrade; Rayssa Aline Rocha Teixeira; Marcelo Emersom Costa Santos; Ingrid Barbosa de Mendonça; Deborah Marrocos Sampaio Vasconcelos; Isaac Neto Goes da Silva; Manoel Wanamark David Ferreira Filho; Leonardo Augusto Fonseca Pascoal; Ednardo Rodrigues Freitas (Animal Bioscience)
Objective The study aimed to evaluate the effects of dietary beta-glucan supplementation for gestation and lactation sows of 1st, 2nd or 3rd parity on reproductive parameters, litter performance, milk composition and Brix value of colostrum, hemogram and serum immunoglobulin G concentration of sows and piglets. Methods A total of 78 sows were distributed in a completely randomized design, using a 2×3 factorial scheme. This design included two supplementation levels of beta-glucans (0 and 450 mg/kg) and three parities (1st, 2nd, and 3rd), resulting in six treatments with 13 replicates each. Supplementation was administered from the beginning of gestation until the end of lactation. Results No interaction was observed between supplementation and parity for the analyzed variables. The dietary supplementation of purified beta-glucans did not influence the reproductive performance of sows, litter performance, and the immune response of sows during gestation and lactation. The weight gain and colostrum Brix value were higher (p<0.05) in 2nd and 3rd compared with 1st parity sows. Conclusion Dietary supplementation of beta-glucans for gestation and lactation sows of 1st, 2nd, or 3rd parity did not affect the performance of sows and litters; however, 2nd and 3rd parity sows had heavier litters, greater weight gain in the suckling period, and higher values of colostrum Brix than 1st parity sows.